DESIGN OF STTAL COLLEGE STUDENT FINAL TASK AND RESEARCH PRODUCT INFORMATION SYSTEM BASED ON WEB - Ahmadi Ahmadi; Muchammadil Chafid; Alexander Victor Bukit; Arie Marbandi (JOURNAL ASRO, 2020)
STTAL is an educational institution to improve the student capability in managing naval technology. Annually, STTAL graduates diplomas and produces final task from the research of students. This product will then be exhibited at official exhibitions of the Indonesian Navy. The information system is designed for the final project and research of STTAL students. This information system is web-based to facilitate the information about the tools that are displayed and will help exhibition crews in conveying information about the tools to the visitors. This information system is easy to use, by scanning the QR Code on the device by Android smartphone application. Keywords : STTAL student work, Final Project Product Information System and STTAL Student Research Based on Web, Android Smartphone, QR Code.